Community Empowerment in the Food Security Program (Construction of Farm Business Roads) in Totolan Village, West Kakas District, Minahasa Regency - Karuyan, Gretty Amelia; Wawointana, Thelma; Mamonto, Fitri H (JUPE : Jurnal Pendidikan Mandala, 2023)
This article discusses community empowerment in the food security program (a case study of farming road construction in totolan village, kakas barat sub-district, minahasa district) This research aims to describe community empowerment in the construction of farming roads. To analyze the level of empowerment in the process of planning, development, and utilization of the farm road program in Totolan Village, West Kakas District, Minahasa Regency. This type of research is descriptive qualitative. Informants are village heads, village assistants (sub-district assistants), village officials, community leaders, Village Representative Council, and people who work as farmers in Totolan village. Data were obtained through interviews, observation, and documentation. Furthermore, this research was analyzed with data validity techniques using the credibility test, transferability test, dependability test, and confirmability test. The results of this study show that community empowerment in the planning process of the farming road program in Totolan village has gone well. The decision-making process is done in a button up manner. The construction of farm roads has involved local labor and the maintenance scheme is a shared responsibility. Utilization of farm road infrastructure has been going well, this can be seen in the increased flow of transportation of agricultural products. The farm road development program has been carried out and has a positive impact on farmers and road users. Another thing that the government needs to do is to build community awareness and mentality, access to capital and institutions in improving community welfare in Totolan village